'You could, couldn't you?': A preliminary investigation of older people's interaction with a bespoke virtual environment using a gesture interface. Issue 3 (1st September 2013) - McSeveny, Kerry; Heller, Ben; Light, Ann; Machaczek, Katarzyna Karolina
This study is a preliminary investigation of whether exploring and interacting in a virtual world, using a customized gesture-based interface, can encourage physical activity in an older population. Older people were consulted to find out what features of a virtual world would appeal to them. Informed by this consultation, a garden was implemented in Second Life. In order to allow users without IT experience to access the garden, and to provide a stimulus for physical exertion, a gesture interface was developed to allow small user movements to control larger or faster avatar movements. We termed this system Second Lives for the Third Age (SL3A). Preliminary evaluation was performed with two older female users. They were both able to use SL3A, despite some difficulties caused by excessive speed of some avatar responses. One user was positive and the other was indifferent about the relevance of such a system to them.